Hypocotyl growth during seed germinaton in Lupinus angustifolius : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Botany at Massey University - Pomeroy, Rachel Elizabeth (Massey University, 1978)
Hypocotyl growth during seed germination in Lupinus angustifolius cv. New Zealand Bitter Blue was studied. There was an initial period of rapid hypocotyl elongation over the whole length of the hypocotyl from 0.5 to 1.5 days. Cell division in the cortex occurred between 1 and 3 days, with a peak at 1.5 days. Total hypocotyl length increased rapidly from 2 to 4 days. The distribution of regions of elongation within the hypocotyl changed during this expansion phase, with a wave of cell elongation proceeding acropetally from the base. The embryo hypocotyl in the seed contained 50 % of the maximum amount of RNA found in the germinating hypocotyl. The peak rate of RNA synthesis for the hypocotyl as a whole, occurred at 12 hours. RNA content of whole hypocotyls doubled between 0.5 and 1.5 days. Nucleoli reached their maximum size within the first day of germination. The loss of vacuoles and granular zones accounted for the subsequent decrease in nucleolar size. At the time of maximum nucleolar size, the nucleus was often convoluted and the nuclear membrane had a high frequency of pores. Cytoplasm was densely packed with polyribosomes and rough e.r. until the cells started their rapid elongation phase at approximately 2 days. RNA synthesis declined rapidly after this time.
Keywords: Lupinus angustifolius; Legumes -- Preharvest sprouting